Proceedings of the 3rd Conference on Physical Modeling for Virtual Manufacturing Systems and Processes - Aurich, Jan C.; Garth, Christoph; Linke, Barbara S. (Springer International Publishing : Imprint: Springer, 2023)
This is an open access book reporting the results of nine years research of the International Research Training Group (IRTG) 2057, funded by the German Research Foundation (DFG). The IRTG is a joint venture between the TU Kaiserslautern, the University of California Berkeley, and University of California Davis. The book is content-driven mainly by two disciplines: engineering and computer science. Through the application of scientific knowledge and advanced computer-based methods in conjunction with physical models on a level unrealized in the past, technologies and methods are promoted, which can be used for planning and optimization of manufacturing systems and processes. As a result, fundamental understanding as well as extensive systems, tools and computational algorithms, which significantly improve the integration of advanced computational methods for solving problems of manufacturing systems and processes will be available. This open access book is of interest to any researcher dealing with process and factory planning in manufacturing, like for cutting and additive manufacturing.